Use of antibiotic therapy for recurrent urinary tract infections caused by Escherichia coli - Stefanović, Tanja; Stojkovic, Eva (General Practice, 2024)
Introduction: Urinary tract infections (UTIs) are among the most common infections and a leading reason for antibiotic prescriptions. They are more common in women,particularly during menopause. The cost of treating urinary tract infections significantly impacts the health system and affects the quality of life, especially when the infections are recurrent. Reinfections account for 80% of recurrent infections, with the primary cause usually being the colon bacterial flora, with Escherichia coli as the dominant culprit.Case report. A 63-year-old female patient visited her GP with complaints of low-grade fever and frequent urination without dysuria. She was diagnosed with cystitis and was prescribed a seven-day course of antibiotics, which effectively resolved her urinary tract infection symptoms. Due to frequent urinary tract infections, she was subsequently placed on a prophylactic six-month course of nitrofurantoin, 50 mg. The patient remained symptom-free during the antibiotic prophylaxis.Conclusion. Many protocols have been shown to reduce the occurrence of urinary tract infections. Antibiotic treatment based on the antibiogram, as well as antibiotic prophylaxis (continuous and post-coital), has proven to be the most effective method for preventing recurrent cystitis. The choice of treatment method and approach depends on the frequency and severity of symptoms.
Keywords: recurrent cystitis; antibiotic therapy; prophylaxis